Job satisfaction and work environment with happiness among Indonesian police personnel - Nenda Valentina Tarigan; Siti Aisyah; Sjahril Effendy (INSPIRA: Indonesian Journal of Psychological Research, 2023)
This study aimed to determine the relationship between job satisfaction, work environment, and personnel happiness. The method used is quantitative descriptive correlative type, which takes samples using proportional random sampling totaling 109 people. In collecting data, it used instruments of job satisfaction, work environment, and personnel happiness, then tested it with multiple linear regression formulas. The results of the research data analysis show there is a relationship between job satisfaction and personnel happiness. There is a relationship between the work environment and personnel happiness, and there is a relationship between job satisfaction and the work environment with personnel happiness. Seeing the relationship between job satisfaction and work environment with personnel happiness, it is hoped that the leadership of Tebing Tinggi Police Station will pay attention to providing increased awareness that supports the creation of happiness in personnel members. These theoretical findings can be used to develop empirical quantitative research in psychology.